Child’s right to be Heard in Chilean Family Courts: Confidential Hearing - Elena Salum Alvarado; Sara Salum Alvarado; Ricardo Saavedra Alvarado (Revista Latinoamericana de Derechos Humanos, 2016)
This work addresses the views family court judges have on The Right of Children to be heard (0-14 years) and the importance they give this as one of the components of the Best Interests of the Child. This qualitative study is framed into the empirical Legal Sociology. To this effect, semi structured interviews to Family Court Judges were applied, focusing on Family Courts processes, specifically in the Confidential Hearing Audience. We argue that there would be a misalignment between the legislation which aims to give life to the Convention on the Rights of the Child’s guiding principles and Family Courts, specifically, on how this legislation plans on implementing the right to be heard.